The Synthesis of Epiboxidine and Related Analogues as Potential Pharmacological Agents - Kulu, Irem; Ocal, Nuket (WILEY-BLACKWELL, 2011)
Methyl epiboxidine-N-carboxylate (8) was synthesized from 7 under reductive Heck conditions (Scheme 2). The C?C coupling of the new epiboxidine analog 9 with aryl and heteroaryl halides gave by hydroarylation C-aryl, N-(3-methylisoxazol-5-yl)-substituted tricyclic imides 10a10f (Table). The [3+2] cycloaddition of 9 with nitrile oxides yielded the bridged dihydroisoxazole derivatives 11a11d with potential biological activity (Scheme 4).
Keywords: Heck reaction; Cycloadditions; Epiboxidine; N-(methoxycarbonyl)-; Isoxazolines; DOMINO-HECK REACTIONS; EPIBATIDINE; SYSTEMS; CHEMISTRY; AFFINITY